Birdwatching Potential Based on Distribution of Bird Diversity in Protected Forests RPH Sumbermanjing Kulon KPH Malang - Iqbal Nur Ardiansyah; Rizky Tania Matovani; Devi Anggar Pertiwi; Ghina Salsabila; Nirmala Ayu Aryanti (Media Konservasi, 2019)
Areas with natural forest potential that are still preserved have the potential to birdwatching activities, a concept of sustainable tourism to preserve the environment and increase the participation of local communities. Protected forests in the South Malang area are natural forests which are still protected by habitat conditions for wild animals, especially for bird species. The purpose of this study was to determine the potential development of a birdwatching track based on the distribution of birds in the Protected Forest Area of Sumbermanjing Kulon KPH Malang. Make a path of observation and identify the types of birds found in protected forests. Knowing the community's response to birdwatching activities around protected forests through interviews. Data analysis was done by making a map of the distribution of maps and the potential of the observation pathway using the ArcGis 10.3 program. There are 51 species of birds with 3.4 species diversity (H ') in the high category. The potential of 22 birdwatching routes with mostly flat road conditions (59%), sloping (23%) and steep (18%). Bird species that can be found in 6 species of birds for each observation pathway. Knowledge of respondents related to the ability to recognize 3-5 species of birds 40%, recognize 70% birdwatching activities, and 83% of respondents' agree with the development of birdwatching as a tourism. Keywords: birdwatching, ecoturism, Kondang Merak, protected forest